Monitoring Program Kadasan Sapi Bali oleh MUI NTB: Pemberdayaan Ekonomi Berbasis Peternakan - Tamzil, Mohammad Hasil; Hailuddin Badri (Universitas Mataram, 2025)
This monitoring activity was conducted to assess the progress of the community empowerment program over its initial six-month period. The evaluation took place on June 30, 2024, focusing on several key aspects: the condition and design of the cattle enclosure system, feed management, the health and productivity of the livestock, and the performance of the program’s beneficiaries—members of the Barokah Farmer Group. Findings revealed that the livestock were housed in a communal pen made of bamboo with compacted earth flooring. However, the pen was found to be narrow, poorly maintained, and had a roof that was too low. The cattle were fed solely with fresh field grass, without any additional concentrates or supplements. Of the nine cattle observed, eight were in good health, while one showed signs of infection in the left hind leg. Among the eight females, seven were pregnant and one was suspected to be sterile. Despite the structural and feeding challenges, members of the Barokah Farmer Group demonstrated strong motivation and cooperative spirit, indicating promising social dynamics and commitment to the program's goals.